Cyanidin-3-galactoside ameliorates silica-induced pulmonary fibrosis by inhibiting fibroblast differentiation via Nrf2/p38/Akt/NOX4. (May 2022) - Ma, Chuang; Lyu, Mingyue; Deng, Chilu; Liu, Xia; Cui, Yanmin; Shen, Yixiao; Meng, Xianjun; Zhao, Jin
Graphical abstract: Highlights: C3G, the most abundant anthocyanin in A. melanocarpa, exerts beneficial health effects. C3G ameliorated SP-induced pulmonary fibrosis, inhibited fibroblasts activation, and downregulated oxidative stress levels. The mechanism involves the Nrf2, p38, Akt, NOX4 signaling pathways. Abstract: Aronia melanocarpa is rich in anthocyanins with many beneficial effects. Cyanidin-3-galactoside (C3G), the most abundant anthocyanin in Aronia melanocarpa was extracted and applied to silica particle-induced (SP-induced) pulmonary fibrosis mice and transforming growth factor-β-induced differentiation of NIH3T3 fibroblasts cell line to investigate the anti-fibrotic properties and underlying cellular mechanisms. The administration of C3G inhibited fibroblast differentiation through antioxidant effects, thereby reducing SP-induced pulmonary fibrosis. In vivo experiments showed that C3G reduced the fibrous nodules and collagen deposition in the lungs, the level of fibroblast markers, and the secretion of pro-fibrotic factors. C3G can also maintain the balance of oxidation and antioxidant in the lungs of mice, inhibit the phosphorylation of mitogen-activated protein kinase p38 and protein kinase B, down-regulate the level of NADPH oxidase 4 and increase the level of nuclear factor (erythroid-derived 2) like 2 express. The in vitro mechanism study of NIH3T3 cells verified the results of in vivo experiments. These findings emphasized the potential use of C3G as a functional food to alleviate SP-induced pulmonary fibrosis.